Long‐term results of primary stenting for subclavian artery disease. Issue 5 (8th April 2013) - Higashimori, Akihiro; Morioka, Nobuyuki; Shiotani, Shinnji; Fujihara, Masahiko; Fukuda, Keisuke; Yokoi, Yoshiaki
<x xml:space="preserve">Abstract</x> Objectives To evaluate initial and long‐term results of endovascular therapy (EVT) for symptomatic subclavian artery (SCA) disease. Background: EVT for SCA disease has a similar success rate as open surgery, but the long‐term patency of EVT alone is uncertain. Methods We retrospectively studied 59 consecutive patients (42 males and 17 females) with 60 lesions. Mean patient age was 68 ± 10 years. Clinical symptoms were vertebrobasilar insufficiency in 21 patients (35.0%), arm claudication in 20 patients (33.3%), angina pectoris in 12 patients (20%), severe arm ischemia in 3 patients (5.0%), vascular access insufficiency in 3 patients (5.0%), and leg ischemia in 1 patient (1.7%). A total of 57 stents were implanted. All patients were followed up at 1, 3, 6, and 12 months after the procedure and annually thereafter. Results The technical success rate was 93.3%. All patients for whom technical success was obtained received stents. There were four technical failures, all of which were owing to the failure of crossing the wire in occluded lesions. There were no procedure‐related deaths. There were two stroke events (3.4%) and one embolic event (1.7%). Primary patency rates were 94.9, 90.8, and 85.8% at 1, 3, and 5 years, respectively. Conclusions EVT for SCA disease is an effective treatment with regard to initial success rate, clinical efficacy, and long‐term primary patency. This minimally invasive procedure is appropriate as the treatment of first choice for proximal subclavian arterial obstructive disease. © 2013 Wiley Periodicals, Inc.